Crossing and Conversion among North Korean Refugee-Migrants - Jeong, Jin heon (Religions, 2020)
While pivotal in the lives of North Korean refugee-migrants, the role of religion has been largely neglected in most studies. After being exposed to Protestant missionary networks, either while dwelling in Northeast China or en route to the South, about 80 percent of North Korean refugee-migrants arriving in South Korea affiliate themselves with Protestant churches. This implies that they are exposed to Protestant missionary networks either while dwelling in Northeast China or en route to the South. Some who leave South Korea for other countries or seek asylum in non-Korean societies develop their religiosity in various ways and for various reasons, as part of their aspirations, adjustment to new homes, and search for meaning. The present study aims to address this literature gap. Based on long-term ethnographic research with North Korean refugee-migrants living in South Korea, China, and Europe, the two ethnographic vignettes presented in this article represent those who are in Germany and the United Kingdom by discussing the religious encounters and conversions through which North Korean refugee-migrants make their lives and futures. It draws attention to religion as a lens through which the migrants’ negotiation of meanings, new selves and homelands, and hopes for the future can be better illuminated. The findings of this study suggest that when North Korean Christians experience religious conversion during their perilous journeys, it not only helps them to negotiate a new sense of belonging in their host societies, but it also mobilizes them to contest the existing order of things.